Heteronomy as the challenge to nation: a critique of collective and of individual rights - J. R. Morss (Law Text Culture, 2004)
Nation continues to be an embarrassment for the cosmopolitan commentator, whether legally inclined or not. As one manifestation of globalisation’s other the nation refuses to accept its proper place in the progress of world history, as a transient reaction to empire. Like social democracy in Marxism, the epoch of nations was expected to dissolve itself, under the impulse of history, to make way for a higher level of political consciousness: if only the pragmatic regionalism represented by the European Community. Instead the spectre lingers, haunting Europe in particular but elsewhere in general, and threatening to be ‘always with us’ even after the poor have been successfully assimilated or dispersed.